SCIENTIFIC-PEDAGOGICAL CAPABILITIES IN ORGANIZATION OF STUDENTS’ INDEPENDENT WORK (Scientific journal of the Fergana State University, 2023)
This article examines the specific pedagogical features and tasks of organizing students’ independent work in  higher educational institutions, ways of organizing students' independent and creative work on the basis of logical and analytical thinking based on self-control training. An exemplary plan for organizing students' independent work based on an innovative approach is presented.